Reporting and interpreting missing health‐related quality of life data in intensive care trials: Protocol for a systematic review. Issue 6 (30th January 2019) - Kjær, Maj‐Brit Nørregaard; Madsen, Martin Bruun; Møller, Morten Hylander; Egerod, Ingrid; Perner, Anders
Abstract : Background: Health‐related quality of life is often used as a patient‐important outcome in randomized clinical trials in the intensive care unit setting. Missing data are a challenge in randomized clinical trials as they hamper the interpretation of the results, but the extent and handling of missing health‐related quality of life data are unknown. Therefore, we aim to describe and evaluate the extent, pattern, and handling of missing health‐related quality of life data in randomized clinical trials conducted in the intensive care unit setting. Methods: We will conduct a systematic review of randomized clinical trials in intensive care patients that report health‐related quality of life. We will systematically search the Cochrane Library, PubMed, excerpta medica database ovid, and cumulative index to nursing and allied health literature for relevant literature. We will follow the recommendations by the Cochrane Collaboration and the preferred reporting items for systematic review and meta‐analysis statement. We will extract information about missing data, including how the analyses and reporting of missing data were performed. We will assess the risk of systematic errors (bias) and compare the number of nonresponders vs responders in (a) low vs high risk of bias trials and in (b) small (n ≤ 100) vs large randomized clinical trials (n > 100). Discussion: With this outlined systematic review, we will describe the handling of missing health‐related quality of life data in randomized clinical trials in the intensive care unit setting and the impact on the interpretation of results. Systematic review registration: International Prospective Register of Systematic Reviews (PROSPERO): reg. no.: CRD42019118932.